A digital microfluidics platform for loop-mediated isothermal amplification detection - Coelho, Beatriz Jorge (2022)
FEDER (Financial Institute for Regional Development) funds through the COMPETE 2020 Program (POCI-01-0145-FEDER-007728). Inn-INDIGO/0002/2015 RADetect for BV.